Is Global IPv6 Deployment on Track? - Friaças, Carlos; Domingues, Mónica; Veiga, Pedro (Emerald, 2007)
IPv6 has been the subject of a significant amount of research work in the networking field for more than a decade. The main aim of this paper is to discuss the current status of IPv6 deployment. It is not the aim of the authors to provide any breakthrough discovery which can boost IPv6 usage, but instead focus on what has happened in the past and what is currently limiting the IPv6 global deployment. The 6NET project [1], along with other national and international initiatives produced a vast collection of knowledge about the next generation Internet protocol. This work is still to be used massively in order to evolve the Internet into its next generation.
Keywords: IPv6; routing; peering; NAT; Addressing